Atmospheric soundings derived from kilometer-scale climate simulations over North America to initialize idealized simulations of mesoscale convective systems - Prein, Andreas F (PANGAEA, 2020)
Inflow soundings of simulated mesoscale convective systems (MCSs) in the central United States under current and future (end of the century under a high-end emission scenario) climate conditions. These are not observed soundings but are derived from current and future kilometer-scale climate simulations. The simulations, from which the soundings are derived, are described in Liu et al. (2017; https://link.springer.com/article/10.1007/s00382-016-3327-9). More details about how the soundings are derived can be found in Prein et al. (2020; under review). These soundings compare well with observed pre-MCS soundings in the U.S. Southern Great Planes (Wang et al. 2020). The archived soundings are in a format that can directly be read by the Weather Research and Forecasting model (https://www.climatescience.org.au/sites/default/files/WRF_ideal_201711.pdf). Each datafile contains five columns representing different variables and the rows show the changes in the variables through an atmospheric column. The header row variables are from left to right: surface pressure [hPa], surface potential temperature [K], and surface vater vapor mixing ratio [g/kg]. The variables in the second to the last row are fro the left column to the right: height above surface [m], potential temperature [K], water vapor mixing ratio [g/kg], zonal wind speed [m/s], and meridional wind speed [m/s]
Keywords: Atmospheric soundings; mesoscale convective systems.